Advanced control of a multi-sourced multi-level source inverter system for high performance electric vehicles. - Bendyk, Maciej Szymon (Cranfield University, 2016)
At present, electric vehicles are getting very popular and there is a high demand for related technologies. Therefore, car manufacturers are looking for cost- effective solutions to improve the efficiency and performance of drive trains. One of the biggest challenges is to create an efficient, reliable and robust system architecture integrated with energy management systems to maximize its performance. Thus, in the last decade technologies started evolving towards use of higher voltage levels with multiple energy sources, which involve complex control and power electronics capable of performing sophisticated functions. In the quest for a new electric drive-train technology, a system architecture together with power and energy management has been identified as a key area of research. This work investigates problems related to the complexity of energy management for power-limited energy sources to improve performance in the whole operation envelope. The widely accepted solution of using multiple energy storage systems is discussed and found to relate to more complicated and expensive power electronic hardware. Furthermore, to achieve high power with reasonable efficiency it is necessary to use high voltage, which is difficult to attain. This work proposes an electrical system with integrated motor control and energy flow management between multiple electric sources with the aim to increase the power capability of an electric drive train. To reach good performance and high efficiency the multilevel, cascaded Voltage Source Inverter with multiple sources is introduced to provide instantaneous proportional power split and to boost voltage for the electric motor at the same time. Whilst there are existing examples of multilevel inverters with electric motor drives, none of them has successfully found their way to mainstream vehicles due to the intricacy and many unresolved technical challenges. This thesis contributes to the field of power electronics in the following areas. Firstly a detailed mathematical analysis of hybrid cascade multilevel inverter with variable voltage ratio between sources has been performed to find its the sources. Secondly, based on the derived equations a new multilevel inverter control and modulation strategy to increase the transient power capability by distributing power between the battery and ultracapacitors has been developed. The method has been validated first through a simulated model in Matlab/Simulink and subsequently by experimental work on a specifically designed and built hardware platform. The results showed that the proposed architecture with modest increase in complexity can markedly improve the system’s transient power capability, and contribute to higher maximum output voltage availability and at the same time minimize Total Harmonic Distortions and switching losses.
Keywords: Multilevel inverter; multisource; switching strategy; power management; drivetrain; space vector modulation